2021
DOI: 10.1002/ett.4363
|View full text |Cite
|
Sign up to set email alerts
|

Mobile‐fog‐cloud assisted deep reinforcement learning and blockchain‐enable IoMT system for healthcare workflows

Abstract: The Internet of Medical Things (IoMT) is increasingly being used to secure blockchain technology to operate healthcare applications in a distributed network. The applications are mobile and can move from one place to another with different wireless connectivity. However, there are a lot of challenges that are investigated further. For instance, dynamic content values changed during mobile applications during any business goal. The workflow healthcare applications are complex as compared to coarse‐grained and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], the authors suggested local and global searching (simulated annealing and genetic algorithm)-enabled dynamic approaches to solve the offloading and and scheduling problem in IoT networks. The main goal was to reduce local and global search times for scheduling on heterogeneous fog and cloud nodes in the system, establish a secure environment among connected nodes, and minimize attack risk in the IoT network.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], the authors suggested local and global searching (simulated annealing and genetic algorithm)-enabled dynamic approaches to solve the offloading and and scheduling problem in IoT networks. The main goal was to reduce local and global search times for scheduling on heterogeneous fog and cloud nodes in the system, establish a secure environment among connected nodes, and minimize attack risk in the IoT network.…”
Section: Related Workmentioning
confidence: 99%
“…The goal was to execute workflow applications on different nodes in order to minimize the total delay of applications. Existing offloading schemes [ 1 , 4 , 7 ] only focused on coarse- and fine-grained applications. Therefore, there are no particular architectures and schemes for workflow applications.…”
Section: Proposed Security Efficient Offloading and Task-scheduling (...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it interconnects medical devices with healthcare providers such as hospitals, private companies, or medical researchers [ 15 ]. IoMT combines IoT with conventional medical equipment and expands sensing and capabilities [ 16 ]. IoMT has the ability to transmit data across a network without demanding human-to-human or human-to-computer interaction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These methods promote the field of IDPs, yet ignore the overall structure of the protein, which leads to inaccurate prediction results. (ii) More recently, the use of machine learning has increased in the field of bioinformatics, especially to solve problems that are closely related to human life and health [15,16]. Methods to identify IDPs through machine learning, especially deep learning techniques, such as PONDR [17], DISOPRED2 [18], RONN [19], DISKNN [20], IDP-Seq2Seq [21], NetSurfP-2.0 [22], SPOT-Disorder2 [23], and RFPR-IDP [24], have also been developed.…”
Section: Introductionmentioning
confidence: 99%